A Guide to Grand Strategy Studies: Political and Military Perspective - Baybars Öğün (Güvenlik Stratejileri Dergisi, 2022)
This study explores the reasons for the uncertainty of the grand strategy concept. The main starting point of the study is that grand strategy cannot be positioned in a single concept against other related concepts in the literature. To reveal the conceptual uncertainty about grand strategy, some grand strategy definitions based on the strategy-policy relationship in the literature and various conceptual levels are compared. The main arguments of this study are as follows: One of the main reasons for the observed conceptual uncertainty is that grand strategy, which is a kind of strategy, is also accepted as a kind of policy. Moreover, the hierarchical position of grand strategy at the military and political levels has not been clarified. This study presents the definitions of the grand strategy concept and provides a guide for further studies in the literature review. In this respect, the study examines the definitions of the grand strategy concept at two conceptual levels: The first level is presented as “tactics, operations, and strategies” from the military perspective, while the second level is presented as “foreign policy and national security” from the political perspective. This study does not deal with the decision-making processes in which grand strategy is determined or with the factors that affect decision-makers. Within this context, grand strategy is considered hypothetically.